KEADILAN ORGANISASI DAN UPAYA MEWUJUDKAN KEPUASAN KERJA KARYAWAN - Mufti Kemarauwana; Didit Darmawan (Universitas Mahendradatta, 2023)
Organizational management has an important task so that thecompany's operations can continue to run. Management of employees as companyassets becomes part of management. Company management tries not to lose itsemployees by increasing job satisfaction. Various factors that can increase jobsatisfaction are researched and developed. This study aims to determine the roleof distributive justice and procedural justice to be able to develop job satisfaction.This quantitative research was conducted in one of the business entities operatingin Malang City. This study uses the census method as a sample of 60 employeeswho work. Research data obtained through questionnaire responses. Data wereanalyzed by multiple linear regression. The data processing process proves thatdistributive justice has a significant influence on the development of jobsatisfaction. Research also proves that procedural justice plays a significant rolein shaping employee job satisfaction. Together, distributive justice andprocedural justice have a significant impact on increasing job satisfaction.